2000
DOI: 10.1034/j.1600-0668.2000.010001002.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Variability of Endotoxin and 3-Hydroxy Fatty Acids in an Office Building During a Particle Intervention Study

Abstract: Air and dust samples were collected on two floors of an office building during a double-blind particle intervention study to examine spatial and temporal variability of airborne endotoxin over a period of weeks, and to characterize endotoxin activity and lipopolysaccharide (LPS) content in carpet and chair dust. Air samples were collected on multiple days within and across weeks. Dust samples were collected from carpets and chairs one day per week for three weeks. Endotoxin was measured using a Limulus assay. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 16 publications
0
35
4
Order By: Relevance
“…With modern MS equipment, detection limits for the chemical markers are in the picogram range. Our previous studies were conducted in the Western hemisphere, more precisely in the United States (Saraf et al, 1997;Hines et al, 2000) and Sweden (Saraf et al, 1999), and we found that the relative amounts of the different 3-OH FAs in indoor environments varied to some extent depending on the type and location of the sampling sites in the building, which reflects dissimilarities in the species composition of Gramnegative bacteria. In comparison, the marker profiles found in the present study differed much more dramatically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With modern MS equipment, detection limits for the chemical markers are in the picogram range. Our previous studies were conducted in the Western hemisphere, more precisely in the United States (Saraf et al, 1997;Hines et al, 2000) and Sweden (Saraf et al, 1999), and we found that the relative amounts of the different 3-OH FAs in indoor environments varied to some extent depending on the type and location of the sampling sites in the building, which reflects dissimilarities in the species composition of Gramnegative bacteria. In comparison, the marker profiles found in the present study differed much more dramatically.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, muramic acid (a unique peptidoglycan component) is used to measure peptidoglycan and bacterial biomass, whereas ergosterol represents a marker of fungal biomass. We have previously applied this type of analysis to characterize the microbiological community in indoor environments (Saraf et al, 1997(Saraf et al, , 1999Bal and Larsson, 2000;Hines et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…For example, chamber data identify higher levels of symptoms in atopic individuals exposed to the same levels of complex mixtures of VOCs (16,47,48). Atopic individuals respond with a larger decrease in nasal resistance to a defined irritant challenge than do nonatopics (49).…”
Section: Symptoms Without Explained Physiology But With Objective Marmentioning
confidence: 99%
“…Few data suggest that such widespread failure of buildings to meet professional expectations is associated with symptoms, primarily because few studies have been designed to examine this hypothesis, although reviews on this topic (13) do suggest associations with building factors in general. In addition, individual studies suggest the ability to change symptoms based on systematic interventions on moisture content (14,15), particulates (16,17), or known sources (18). This suggests that many of these symptoms may in fact have remediable causes.…”
Section: Unexplained Symptoms With Potentially Explained Mechanismsmentioning
confidence: 99%
“…This result is similar to findings previously reported that enhanced air filtration achieved by installing HEPA filters (estimated Ն95% efficient at 0.3 m) in an office building did not significantly affect airborne endotoxin levels. 39 To optimize the operation of air filters in realistic environments, the energy requirements and costs of replacing filter media and UV lamps need to be estimated. The major operating cost of the HUVAF tested in this study is related to electrical power consumption.…”
Section: Discussionmentioning
confidence: 99%